“Corpo e tempo”. Eros and Melancholy in Gëzim Hajdari’s Transmediterranean Poetics (Ticontre. Teoria Testo Traduzione, 2018)
This article elaborates on the intersection between sensual imagery, melancholy and exophony in Gëzim Hajdari’s Poesie scelte (1990-2007), a self-anthology that presents extracts from nine of his poetic works, collecting together almost twenty years of poetic activity. Firstly, it provides a background to Hajdari’s oeuvre, describing the context for the flourishing of his double language (Albanian-Italian). Secondly, it explores the characteristics of Poesie scelte and the significance of the work within Hajdari’s intellectual journey. Thirdly, it analyses three main themes: otherness, body and eros. While these words are all foregrounding tropes in the collection, they surface with varying intensity in the different stages of Hajdari’s poetics. The analysis illuminates the prevailing of otherness in the first phase; body, in the central phase; and eros, in the mature phase. The examination of sensual tropes in Poesie scelte is read in light of Hajdari’s progressive acquisition of the Italian language, and the development of his exophonic voice, and aims to trace the effect of movement in mobilising sensual imagery within the inner qualities of the versification process.Questo articolo esplora le intersezioni fra immaginario sensuale, malinconia e esofonia nel volume antologico Poesie scelte (1990-2007) di Gëzim Hajdari. Il volume contiene estratti da nove sillogi hajdariane e si configura dunque come un quadro di sintesi di circa vent’anni di attività poetica. Una prima sezione contestualizza la poetica di Hajdari e descrive il progressivo sviluppo della sua lingua doppia (albanese e italiana). Una seconda sezione si concentra sulle peculiarità di Poesie scelte nel quadro della parabola poetica e intellettuale di Hajdari. In una seconda parte l’articolo si concentra su tre parole chiave: alterità, corpo ed eros. Tutti questi termini si configurano come centri semantici nel percorso hajdariano; tuttavia affiorano con vari livelli di intensità in diverse fasi. L’analisi illumina il prevalere di un immaginario proiettato verso una percezione di alterità in una prima fase, verso il corpo in una fase intermedia e verso l’eros in una fase più matura. L’analisi dell’immaginario sensuale e delle figure del desiderio in Poesie scelte è sviluppata in luce dell’acquisizione progressiva dell’italiano da parte di Hajdari e della conseguente evoluzione della componente esofonica e mira a illuminare questi processi nei vari livelli della versificazione.